Вацлав Борейко. До 250-річчя від дня народження - Melnik, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The paper is devoted to life and creative achievement of eminent landscape architect Waclaw Boreyko, who laid botanical garden and four landscape gardens in Ukraine. Modern state of Boreyko’s landscape gardens are described.